2023
DOI: 10.6018/analesps.511201
|View full text |Cite
|
Sign up to set email alerts
|

The social perspective of euthanasia in Spain: variables that predict attitudes towards euthanasia

Abstract: The debate surrounding whether or not euthanasia should be a legal practice has been present in Spanish society since the 90’s. Recently, the Spanish government has passed Organic Law 3/2021 on the regulation of euthanasia.  In relation to this question, which has raised and continues to raise controversy among both public opinion and the political and legal world, this work explores the relation of the different variables to the attitudes of the Spanish public towards euthanasia. For this purpose, 182 people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
(58 reference statements)
1
4
0
Order By: Relevance
“…Additionally, participants with higher level of education and lower level of religiosity manifested more positive attitudes toward EUT in both medical conditions. These findings support former studies which found positive correlations between education levels and attitudes toward EUT ( 18 21 ), and negative correlations between religiosity level and favorable tendency toward EUT ( 5 , 21 , 30 , 31 , 34 , 37 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, participants with higher level of education and lower level of religiosity manifested more positive attitudes toward EUT in both medical conditions. These findings support former studies which found positive correlations between education levels and attitudes toward EUT ( 18 21 ), and negative correlations between religiosity level and favorable tendency toward EUT ( 5 , 21 , 30 , 31 , 34 , 37 ).…”
Section: Discussionsupporting
confidence: 92%
“…Since prevalent religions prohibit all forms of euthanasia and suicide, religious beliefs are important factors in explaining attitudes toward EUT. Most studies reported that religiously observant persons displayed more negative attitudes and behaviors toward EUT and assisted suicide than secular people ( 5 , 21 , 30 , 31 ). However, some variation exists between different religions and religious denominations ( 3 , 18 , 20 , 24 , 32 , 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on research carried out in Spain, there are no differences in attitudes toward euthanasia according to the gender or age of the participants, which does not correspond to our data. However, religion is seen as an important factor influencing the attitude [ 22 ]. Moreover, according to some studies, sociodemographic factors such as religiosity play a greater role in attitudes toward euthanasia than disease severity [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that respondents with a worse academic background tend to support euthanasia more compared to those with higher education [ 25 ], which also corresponds to our findings. Additionally, political orientation may have an impact on the public’s attitude [ 22 ]. A unique study from South Korea identified poor physical status and comorbidity as prognostic factors for acceptance of medical assistance in dying [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Religiosity has been measured in diverse ways, which may be broadly categorized into self-identification issues and participation issues. Self-identification issues include the degree to which respondents conceive themselves as being religious (Balslev van Randwijk et al , 2020; Bulmer et al , 2017; Montañés Muro et al , 2023; Musgrave and Soudry, 2000; Ryynänen, 2002; Sullivan et al , 1998) and the importance they attribute to religion or to God (Inglehart et al , 2021; Periyakoil et al , 2016; Pitt, 2014; Rudnev and Savelkaeva, 2018; Verbakel and Jaspers, 2010). Participation issues mainly refer to adherence to religious practices (Barnett et al , 2020; Bevacqua and Kurpius, 2013; Castelli Dransart et al , 2021), particularly in the case of church/religious institution attendance (Burdette et al , 2005; Danyliv and O’Neill, 2015; DeCesare, 2000; Marsala, 2019; Sikora, 2009; Singh, 1979).…”
Section: Literature Reviewmentioning
confidence: 99%